Digitalization within the informal settlements. Participatory technologies in design for upgrading the informality in Maputo, Mozambique - Ghorbanbakhsh, M. (2022)
Participatory Technologies in design offers an opportunity for architects to re-design cities and find new opportunities, in different scales, with their citizens, to create new economic, social, environmental values and provide better public realms and empowering the community by engaging them in participatory actions, aiming at the sustainability of urban public space and rapidly suppress its insufficiencies. Accordingly, the city and architecture of the future face the challenge of innovation in an evolution that involves society, economy, environment, etc. But what about the informal settlements which are dealing with socio-economic and environmental issues? These neighborhoods present the greatest challenges to human sustainable development and equity, safety, environmental quality, and resiliency central to the New Urban Agenda. As information and communication technology (ICT) becomes pervasive, the architect has to rethink the rules for communication between the citizen and physical urban space for adapting to the period in which we are living in. Over the last few decades, an increasingly collaborative work developed among spatial practitioners such as architects, urban planners, artists and, media designers; has produced a particular landscape of projects that engage information technology as a catalytic tool for interactions in the physical urban space. ICT, mobiles, applications, and digital technologies are tools to empower slum residents and their youth to have greater control over their lives. Communities and prosperity through access to information and knowledge are going to be more engaged and empowered. Basically, to develop a public realm or neighborhood or a barrio, the first tool is data. Architects and decision-makers will be the data users. Moreover, citizens will be the Data collectors and, in this system, they can get aware of individual impacts on themselves and the whole. Enabling communities to participate in settlement planning and upgrading including, the management of new infrastructure undoubtedly, requires action at the political level but, we cannot hesitate architect’s role to society aim to provide lasting solutions to specific needs and, the active participation of the community lends these additional values. In this context, the proposed paper will present an overview of the participatory digital technologies involved in civic engagement in informal cities in Africa. This analysis is essential to define the application of spatial acupunctures or plug-ins in the public realm and urban environment to upgrade the informality in Maputo, Mozambique.